The Role of Physical Education in Preventing Obesity in Elementary School Children - Tasya, Amalia (Journal of Salutare, 2025)
Obesity in elementary school age children is a global health problem that can have an impact on increasing the risk of chronic diseases and reducing children's quality of life, physical education as part of the school curriculum is seen as having an important role in preventing obesity by increasing physical activity, fitness, and forming healthy living habits from an early age. This study aims to analyze the role of physical education in the prevention of obesity in elementary school children and examine the factors that affect its effectiveness, including aspects of nutrition, child awareness, socio-economic, and educational policies. The method used is Systematic Literature Review (SLR), a literature search is conducted on international databases such as PubMed, Scopus, and Web of Science for publications in 2020–2025, from the results of identification, screening, and full review, 23 articles that meet the inclusion criteria are obtained, including 11 main articles relevant to the research focus. The results of the study show that formal physical education is the most influential variable in reducing the prevalence of obesity in children, especially if it is carried out regularly, intensively, and integrated with nutritional interventions and child awareness improvement programs. Socio-economic factors were found to have an inconsistent influence, while single nutrition education and awareness without physical activity proved to be less effective, and education policy support played a very important role in ensuring the success of the program